Experimental study on two-level yielding buckling-restrained braces. (August 2019) - Li, Guo-Qiang; Sun, Ying-Zhi; Jiang, Jian; Sun, Fei-Fei; Ji, Chang
Abstract: Buckling-restrained braces (BRBs) are widely used in engineering especially for braced frames as load-bearing as well as excellent energy dissipating members. However, the conventional BRBs are designed in elastic state under frequent earthquakes for avoiding low-cycle fatigue, and cannot contribute to seismic energy dissipation. In order to overcome this defect, conventional BRBs are recommended to combine with metal tube dampers to form a novel type of two-level yielding buckling-restrained braces (TYBRBs). The tube damper in TYBRBs yields under frequent earthquakes to consume seismic energy. The core plate of TYBRBs yields under rare earthquakes to further dissipate energy and reduce seismic effect. In this paper, the configuration and mechanical models of TYBRBs are first presented. Two TYBRB specimens are designed and cyclic loading tests are carried out. It is found that: (1) the low-cycle fatigue resistance of tube dampers can meet the requirements of TYBRBs for frequent earthquake resistance; (2) The functions of TYBRBs can be realized with rational design; (3) The performance of BRBs in TYBRBs does not degrade with combination of tube dampers. Highlights: A new type of two-level yielding buckling-restrained braces (TYBRBs) was proposed. The two-level yielding function of TYBRBs was confirmed by the experimental research. Under frequent earthquakes with small displacement, the tube damper yields and the core plate remains elastic. The proposed mechanical model is in good agreement with properties of TYBRBs. After failure of the tube damper, the core plate can bear the load independently.